1982
DOI: 10.1073/pnas.79.19.5901
|View full text |Cite
|
Sign up to set email alerts
|

Molecular structure and evolutionary origin of human cardiac muscle actin gene.

Abstract: Two recombinant phages that contain cardiac muscle actin gene were isolated from a human DNA library and their structures were determined. Restriction analysis indicates that both clones carry the same EcoRI 13-kilobase fragment where the coding sequence is mapped. The cloned DNA hybridized with polyadenylylated RNA from human fibroblasts, which directs the synthesis of cytoplasmic beta- and gamma-actin in vitro. However, sequence determination of the cloned DNA showed that the entire coding sequence perfectly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0

Year Published

1983
1983
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(79 citation statements)
references
References 29 publications
7
72
0
Order By: Relevance
“…We have demonstrated that the human fibroblast p-and y-actin genes do not encode a cysteine immediately following the MET initiation codon, unlike human a actin (this work) or cardiac actin (11). This result strongly suggests that two discrete actin gene types gave rise to the deuterostome actins, but this result also raises an unsettling evolutionary paradox.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…We have demonstrated that the human fibroblast p-and y-actin genes do not encode a cysteine immediately following the MET initiation codon, unlike human a actin (this work) or cardiac actin (11). This result strongly suggests that two discrete actin gene types gave rise to the deuterostome actins, but this result also raises an unsettling evolutionary paradox.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast, the demonstration of this encoded residue in chick a (6), rat a (29), human cardiac (11), and now human a actin (this work), in addition to all six Drosophila actin genes (7), raises the possibility that this residue is intimately involved in muscle actin gene expression. If this cysteine is post-translationally removed in all cases, as it clearly is in chicken (6) and mammals (26,29), then this residue may serve a regulatory rather than a structural role in actin expression.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Hybridization and wash conditions have been previously described [21]. Membranes were stripped and reprobed with a p-actin probe [27]. Results were expressed as the CYP3A4 RNA/actin RNA ratio.…”
Section: Methodsmentioning
confidence: 99%
“…These elements have the potential to adopt alternative DNA conformations that might direct the binding of transcription factors or other regulatory proteins to sites in the promoter [28].…”
Section: Figure 2 Determination Of Cres Transcription Start Sites By mentioning
confidence: 99%